How parental mediation affects adolescents’ problematic smartphone use: the chain mediating role of basic psychological needs and positive outcome expectations - Chen, Yan; Gu, Qian; Zheng, Qishan; Hu, Biying; Gu, Chuanhua; Hu, Qingping; Cao, Yuqi (Frontiers in Psychology, 2025)
PurposeProblematic smartphone use can significantly jeopardize adolescents’ academic development as well as their physical and mental health. Although previous studies have explored the role of parental mediation strategies in adolescents’ problematic smartphone use, the underlying mechanisms remain unclear. This study aims to investigate the relationship between parental mediation and adolescents’ problematic smartphone use, with a specific focus on the chain mediation effects of basic psychological needs and positive outcome expectations.MethodsThis study conducted a cross-sectional survey of 1,947 students from three junior high schools in Wuhan, Yichang, and Xiaogan, China, using a cluster sampling method. Validated scales were employed to measure parental mediation, problematic smartphone use, basic psychological needs, and positive outcome expectations.ResultsThe findings revealed that active mediation not only directly influences problematic smartphone use but also exerts an indirect effect through the individual mediation of basic psychological needs and positive outcome expectations, as well as through the sequential mediation from basic psychological needs to positive outcome expectations. Parental supervision not only directly influenced problematic smartphone use but also exerted indirect effects through the independent mediating role of basic psychological needs and the chain mediation pathway from basic psychological needs to positive outcome expectations.ConclusionActive mediation and basic psychological needs significantly reduced adolescents’ problematic smartphone use, whereas parental supervision and positive outcome expectations significantly increased it. These findings provide theoretical insights into the mechanisms of problematic smartphone use and offer practical implications for educational strategies, emphasizing the importance of parents selecting appropriate mediation approaches, fulfilling basic psychological needs, and reducing positive outcome expectations to mitigate adolescents’ problematic smartphone use.